Aldehyde dehydrogenase 2 deficiency significantly exacerbates tert‐butyl alcohol‐induced toxicity in mice. Issue 7 (14th February 2020) - Lin, Liping; Suda, Megumi; Xu, Chenlan; Zhang, Yuehan; Yanagiba, Yukie; Nie, Jisheng; Nakajima, Tamie; Weng, Zuquan; Wang, Rui‐Sheng
Abstract: Owing to the use of ethyl tert ‐butyl ether (ETBE) as a fuel additive, the possible adverse effects of ETBE exposure have become a public concern. Our previous study showed that ETBE‐induced toxicity in aldehyde dehydrogenase 2 ( Aldh2 ) gene knockout (KO) mice was caused by its primary metabolite acetaldehyde, which was toxic. However, it is unclear whether tert ‐butyl alcohol (TBA), another main metabolite of ETBE, plays a role in ETBE‐induced toxicity. To investigate this relationship, we analyzed the changes of TBA concentrations in tissues after ETBE exposure, and then evaluated the toxicity after direct TBA treatment in both KO and wild‐type (WT) mice. An exposure to 500 ppm ETBE via inhalation resulted in the formation of its three metabolites, TBA, 2‐methyl‐1, 2‐propanediol and ethanol, whose concentrations in the liver, brain, fat and testis of male KO mice were significantly higher than the corresponding concentrations observed in male WT mice. Direct treatment to TBA (20 mg/mL of drinking water) caused significant changes in relative organ weights and histopathology, and increased levels of genetic damages in both types of mice. These toxic effects were also seen in KO mice exposed to a lower concentration of TBA (5 mg/mL), which was associated with increased oxidative stress in serum (reduced glutathione and reduced glutathione/oxidized glutathione ratio decreased). Our findings indicate that ALDH2 is involved in the metabolism of ETBE and TBA, and ALDH2 deficiency could greatly increase the sensitivity to TBA‐induced toxicity. Abstract : We found that aldehyde dehydrogenase 2 (ALDH2) deficiency could increase the concentration of tert ‐butyl alcohol (TBA) in tissues such as liver and testes in ethyl tert ‐butyl ether (ETBE)‐exposed mice. Furthermore, DNA damage, oxidative stress and tissue toxicity in the ALDH2‐deficient mice were enhanced after exposure to TBA. These results showed the important role of ALDH2 in the metabolism and toxicology of ETBE and its metabolite TBA.